Dietary L-tryptophan supplementation alleviates ammonia-induced stress in Nile tilapia fingerlings - Eman Y. Mohammady; Amina Y. Kamal; Mohamed A. Elashry; Abdelkarim I. M. El-Sayed; Mohamed S. Hassaan (Scientific Reports, 2025)
Abstract L-tryptophan dietary supplementation is a useful tactic to increase aquatic animals’ energy stores and antioxidant capability, thereby enhancing their resistance to environmental stressors like ammonia stress. Therefore, the present study aims to investigate the influence of tryptophan supplementation on the growth in Nile tilapia as well as the protective efficiency of tryptophan on blood indices, immune response, and antioxidant status against ammonium chloride (NH 4 Cl) stress. Fish were fed levels of tryptophan diets (0, 2 g, 4 g, and 8 g/kg diets) for 70 days after which fish were exposed to total ammonia (TA-N) (0 and 5 mg/L; 0.35 NH 3 –N) for 10 days. The study found that higher dietary L-tryptophan levels led to a linear increase in final body weight ( P = 0.031), weight gain ( P = 0.045 ), and specific growth rate ( P = 0.032) in Nile tilapia fish. However, dietary supplementation with L-tryptophan at 4 and 8 g/kg significantly improved various physiological parameters in fish, irrespective of ammonia (NH 4 Cl) exposure. Notably, the 8 g/kg dosage yielded the most pronounced benefits ( P < 0.05). L-tryptophan enhanced hematological health by elevating hemoglobin, hematocrit, red blood cells, white blood cells, and lymphocytes ( P < 0.05). It also alleviated NH 3 –N stress by lowering liver enzymes (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase), cortisol, and glucose levels, while improving total protein, albumin, globulin, and nitric oxide concentrations ( P < 0.05). Additionally, hepatic antioxidant status improved, as seen by increased superoxide dismutase and glutathione levels, with the highest levels recorded in fish fed on the 8 g L-tryptophan/kg diet and exposed to ammonia, and reduced malondialdehyde content ( P < 0.05). Moreover, L-tryptophan supplementation enhanced immune responses in fish exposed to NH 3 -N, as indicated by increased levels of complement component (C3 and C4), and IgM ( P < 0.05). These results suggested that L-tryptophan (8 g/kg diet) plays a protective and enhanced role in the growth, immunity, and antioxidant status of Nile tilapia under stress conditions such as ammonia exposure.